Ստեփանոս Օրբելյան, «Պատճառ տաւնի սրբոյ հոգւոյն» - Թերզյան, Գայանե
Step‘anos Ōrbelean’s (1250-1303) extensive theological Controversy Against the Diophysites is one of his important works, completed in the final year of his life, 1302. It was published in Constantinople in 1756. However, the chapter entitled “The ‘Cause’ of the Holiday of the Holy Spirit” is absent from the edition, wherein the author rejects the eight-day celebration of the Pentecost, remaining faithful to the centuries-old tradition of the Armenian Church. Presumably, until the 12th century, the Armenian Church observed the Pentecost with a one-day celebration. Later, under the influence of the Chalcedonian Church, the Armenian Church adopted the eight-day celebration of the Pentecost, a tradition that has been preserved to this day. In this article, we present the critical edition of the chapter “The ‘Cause’ of the Holiday of the Holy Spirit” based on three manuscripts preserved in Matenadaran. Труд Степаноса Орбеляна (1250-1303 гг.) «Возражение против диофизитов», написанный им в последний год жизни – одно из самых важных его сочинений. Он был издан в Константинополе в 1756 году. В издании отсутствует последняя глава – ««Причина» Дня Святого Духа», в которой автор критикует восьмидневное празднование Дня Святого Духа (Пятидесятница). Предпо- ложительно до XII века Армянская Церковь отмечала День Святого Духа однодневным празднованием. Позднее под влиянием Халкидонской Церкви в Армянскую Церковь вводится восьмидневное празднование, сохранившееся до сих пор. В статье представлен критический текст главы ««Причина» Дня Святого Духа», составленный по трем рукописям, хранящимся в Матенадаране им. Месропа Маштоца.
Keywords: Հրապարակումներ; Գրական վերլուծություն